A Journey into a River - Johnson, Rebecca L. (Minneapolis Carolrhoda Books, Inc., 2004)
Takes readers on a journey into a river, showing examples of how the animals and plants are connected and dependent on each other and the river's freshwater environment.
1 - 6
Keywords: Stream ecology; Rivers; Ecology; Biomes of North America